2019
DOI: 10.2478/prolas-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Role of Pathological Personality Traits in the Prediction of Suicidal Ideation in General and Psychiatric Inpatient Sample

Abstract: The aim of this study was to evaluate the utility of the pathological personality traits in predicting suicidal ideation, especially in combination with other risk factors, such as the level of depression, prior attempts of suicide, low self-esteem, low level of perceived social support and self-esteem-by-social support interaction, both in general and in psychiatric inpatient samples. Data were analysed within two samples: non-clinical general sample (n = 461) and psychiatric inpatient sample (n = 131). Latvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The group of people at high risk of suicide had higher scores in pathological traits, measured with idcp-2 and with pid-5, compared to the other sample groups, confirm the findings of previous studies regarding depression and submissiveness (Perepjolkina et al, 2019), impulsivity (Peters et al, 2016), hopelessness (Beck et al, 1985), vulnerability and self-devaluation (Fergusson et al, 2003). Besides, our results indicated that borderline pd traits are more associated with suicidal behavior compared to other investigated pathological traits, confirming previous findings (Paris, 2002;Winsper et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The group of people at high risk of suicide had higher scores in pathological traits, measured with idcp-2 and with pid-5, compared to the other sample groups, confirm the findings of previous studies regarding depression and submissiveness (Perepjolkina et al, 2019), impulsivity (Peters et al, 2016), hopelessness (Beck et al, 1985), vulnerability and self-devaluation (Fergusson et al, 2003). Besides, our results indicated that borderline pd traits are more associated with suicidal behavior compared to other investigated pathological traits, confirming previous findings (Paris, 2002;Winsper et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Although the specific mechanisms are not yet known, the origin of suicidal behavior occurs through the interaction of several factors, as biological, psychological, social, and environmental (O'Connor & Kirtley, 2018). Among the psychological factors related to suicidal behavior, studies have highlighted the pathological personality traits (Brezo et al, 2008;Jaksic et al, 2017;Perepjolkina et al, 2019;Pompili et al, 2005;Raczek et al, 1989). Evidence indicates an increased risk of suicide in people with personality disorders (pd) and an in people with high scores on pathological traits (Arsenault-Lapierre et al, 2004;Björkenstam et al, 2016), especially for borderline pd (Paris, 2002;Winsper et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To what extent is this item understandable and transparent to an emergency technician? Each question was scored on a Likert scale from very low to very high (1)(2)(3)(4)(5). Experts answered all of these questions for each protocol item.…”
Section: Protocol Developmentmentioning
confidence: 99%